Meningkatkan Hasil Belajar Geografi Siswa Kelas X IPS 2 SMA Negeri 2 Pasarwajo Dengan Menggunakan Model Problem Based Learning - Wa Rati; Surdin; La Ode Nursalam (Jurnal Penelitian Pendidikan Geografi, 2022)
Senior high school 2 Pasarwajo is one of the schools in Pasarwajo District, Buton Regency which is the object of research because the results of learning geography are still low as seen from the daily test scores of students who still have not reached the KKM. This is because the teachers who teach still use conventional methods in the form of lectures so that students become passive. The aims of this study are: 1) to describe student learning activities by applying the Problem Based Learning model; 2) to describe teacher teaching activities by applying the Problem Based Learning (PBL) model; and 3) to find out the increase in geography learning outcomes for class X IPS 2 SMA Negeri 2 Pasarwajo by applying the PBL model to the material on the Dynamics of the Planet Earth as a Space for Life. This research is a class action research (CAR) which was carried out in two cycles. The subjects of this study were teachers and students of class X IPS 2. Learning outcomes were measured using observation sheets and learning achievement tests. The results showed that: 1) in cycle I, the average score obtained from student activity was 2.5 in the sufficient category and increased to 3.4 in the good category in cycle II; 2) in cycle I the average score obtained from the teacher's teaching activities was 2.6 in the sufficient category and increased to 3.5 in the good category in cycle II; 3) student learning outcomes increased by 18% after applying the problem based learning model from cycle I student learning outcomes increased by 64% to increase by 82% in cycle II.